Implementasi Corporate Social Responsibility dalam Mendukung Kemandirian Masyarakat Lokal - Ervandra Rendy Pratama; Luluk Dwi Kumalasari (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes the implementation of Corporate Social Responsibility (CSR) by SIG Pabrik Tuban in supporting local community independence. CSR is not only a corporate social responsibility but also a strategy to build harmonious relationships with the community and ensure economic sustainability. A descriptive qualitative method is applied in this research, with data collected via interviews, observations, and literature studies. The findings indicate that the company's CSR programs focus on economic empowerment, capacity building, and infrastructure development with a strategic allocation of funds. Through collaboration with the Forum Masyarakat Kokoh (FMK), CSR programs are designed based on community needs to enhance effectiveness and sustainability. CSR implementation has been proven to improve community skills, expand economic access, and strengthen the local business ecosystem. With a participatory and systematic approach, CSR at SIG Pabrik Tuban plays a crucial role in fostering a more independent and empowered society. These efforts highlight the importance of corporate involvement in sustainable development and community welfare.